The optical photometric and spectroscopic investigation of Type IIP supernova 2012A. Issue Volume 9:Issue S296(2013) (29th January 2014) - Roy, Rupak; Sutaria, Firoza; Bose, Subhash; Johnson, Sean; Dwarkadas, Vikram; York, Brian; Kumar, Brijesh; Kumar, Brajesh; Bhatt, Vijay K.; Chakraborti, Sayan; York, Don; Ritchey, Adam; et al.
Abstract: Supernova 2012A was discovered on 7.39UT, January, 2012 in the nearby galaxy NGC 3239 at an unfiltered magnitude of 14.6 and classified spectroscopically as a Type IIP event. Here, we present the optical photometric and spectroscopic follow-up of the event during 14d to 130d post explosion.